The Changing Returns to Crime: Do Criminals Respond to Prices? - Mirko Draca; Theodore Koutmeridis; Stephen Machin (Institute for the Study of Labor (IZA), 2015)
In economic models of crime individuals respond to changes in the potential value of criminal opportunities. We analyse this issue by estimating crime-price elasticities from detailed data on criminal incidents in London between 2002 and 2012. The unique data feature we exploit is a detailed classification of what goods were stolen in reported theft, robbery and burglary incidents. We first consider a panel of consumer goods covering the majority of market goods stolen in the crime incidents and find evidence of significant positive price elasticities. We then study a particular group of crimes that have risen sharply recently as world prices for them have risen, namely commodity related goods (jewellery, fuel and metal crimes), finding sizable elasticities when we instrument local UK prices by exogenous shifts in global commodity prices. Finally, we show that changes in the prices of loot from crime have played a role in explaining recent crime trends.
Keywords: K42; 330; crime; goods prices; metal crime; commodity prices